Students Perception of Science and Technology in Science Learning: A Gender Comparative Study - Putri, Atila Ledia; Pranata, Ogi Danika; Sastria, Emayulia (Jurnal Pijar Mipa, 2024)
Teachers face a dilemma. On the one hand, science and technology significantly benefit students, providing greater opportunities for future generations. On the other hand, students' interest in science and technology continues to decrease. The rapid advance of science and technology also widens inequities and enhances gender differences. Understanding students' perceptions of technology in learning, especially science, and their daily lives is necessary. The research employs both descriptive and comparative methods as its primary methodologies. The descriptive method provides an overview of students' perceptions of science and technology. The comparative method helps uncover differences in students' perceptions based on gender. The study encompasses 200 participants from a junior high school in Kerinci. This research utilized the "My Opinions about Science and Technology" questionnaire. The questionnaire was translated into Indonesian and formatted into an online survey using Google Forms. It comprises 16 research statements about science and technology designed to collect essential data, employing a 4-point scale response. The Independent Samples T-test, facilitated by SPSS, compared male and female perceptions of science and technology. The descriptive statistics reveal that the average student perception is 3.06. Based on the level of each student, no students are categorized as having a low level of perception of science and technology. Based on gender, female students exhibit an average perception of 3.02, and males display an average of 3.11. Based on the mean or average values, it can be concluded that there is a difference in the average perception between female and male students, with male students showing a higher perception of science and technology than female students. The independent samples t-test results confirm that the average perception of females regarding science and technology is lower than that of males, with a mean difference of -0.093 on a 4-point scale. The disparity in perception based on gender was found to be statistically significant. Male students have a higher percentage of high-level perception compared to female students. Males exhibit high perceptions regarding the development of scientific theories, the impact of science and technology on environmental problems, and the potential for science and technology to improve life, create more interesting jobs and help eradicate poverty and famine. The theoretical and practical implications of these results are discussed.